2022
DOI: 10.3390/membranes12030326
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Two Stabilizers in Nanoemulsions with Whey Proteins and Thyme Essential Oil as Edible Coatings for Zucchini

Abstract: Edible coatings are important for horticulture crops preservation and reducing food waste. Application of edible coatings followed by low-temperature storage prolongs the storability, preserves quality, and decreases the overall postharvest losses. This study evaluated the efficacy of two nanoemulsions formulae containing thyme essential oil and whey proteins as coatings for zucchini, with the purpose of extending their shelf-life. The nanoemulsions were rheologically evaluated and the formula with guar and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Concerning zucchinis, some studies focus on the possibility of extending their SL improving the conservation with different approaches. For example, the effect of different coatings on the quality of fresh zucchini during storage was investigated by evaluating physicochemical, visual [ 17 ] and sensorial properties [ 18 ]. The effects of individually shrink wrapping zucchini fruits on different quality parameters, namely cold tolerance, chilling injury, the loss of weight and firmness during storage at 4 °C, were also investigated [ 19 ] as well as the effects of other different treatments on fresh zucchini.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning zucchinis, some studies focus on the possibility of extending their SL improving the conservation with different approaches. For example, the effect of different coatings on the quality of fresh zucchini during storage was investigated by evaluating physicochemical, visual [ 17 ] and sensorial properties [ 18 ]. The effects of individually shrink wrapping zucchini fruits on different quality parameters, namely cold tolerance, chilling injury, the loss of weight and firmness during storage at 4 °C, were also investigated [ 19 ] as well as the effects of other different treatments on fresh zucchini.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GA has a low viscosity with high emulsification properties and strong stability, which can be used as an excellent film-forming material in food and non-food applications, e.g., bakery, beverages, fruits and vegetables, pharmaceuticals, and cosmetics (Kawhena et al, 2021;Taher et al, 2022). The effects of GA as an edible coating on the quality and shelf life of tomato (Ali et al, 2013), summer squash (Bleoanca et al, 2022), plum (Fawole et al, 2020), pomegranate (Kawhena et al, 2021), kaki (Saleem et al, 2023), peach (Taher et al, 2022), apple (Soppelsa et al, 2023), acid lime (Beheiry et al, 2023), strawberries (De Bruno et al, 2023), guava (El-Gioushy et al, 2022), banana (Maqbool et al, 2011), and papaya (Maqbool et al, 2011) have been investigated. The findings of the previous studies revealed that coating with GA delayed the ripening, decreased weight loss, reduced shrivel, postponed microbial spoilage, preserved the antioxidants, lowered browning and chilling damage, and prolonged the shelf life of fruits during storage.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EOs' high volatility, oxidizability, and thermosensitivity call for alternative protection techniques to counteract these negative traits. Several techniques are available for EO protection that are already used for active packaging, like their inclusion in composite materials (e.g., zeolite-thymol antimicrobial composites [13]); nanoemulsion formation (e.g., EF/TEO nanoemulsion used for zucchini active coating [14]); thymol nanoemulsion included in gelatin films [15] or encapsulation (e.g., edible coating with encapsulated TEO in liposomal chitosan applied to cheese [16]); and antimicrobial packaging with coriander EO encapsulated in cyclodextrin nano-sponges [17].…”
Section: Introductionmentioning
confidence: 99%